Role of plasminogen/plasmin system components and matrix metalloproteases in retinal artery occlusion following cardiac surgery (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the impact of plasminogen/plasmin system components and matrix metalloproteases (MMPs) on the development of retinal artery occlusion (RAO) after cardiac surgery for valvular heart disease (VHD).Material and Methods: Seventy three patients who underwent cardiac surgery for VHD were included in the study. Of these, 23 patients older than 60 years who had conventional-access mechanical prosthetic valve replacement with cardiopulmonary bypass were stratified into the group of high risk (HR) for RAO. Ten HR patients developed branch or central RAO. The low-risk (LR) group comprised 50 patients younger than 60 years who had valvuloplasty via a minimally invasive approach or the femoral artery using a biological implant. The control group comprised 15 patients who had no cardiac disease. Coagulogram indices and D-dimer were measured. Enzyme-linked immunosorbent assay kits were used to determine plasma plasminogen activator inhibitor (PAI)-1, plasmin-α2-antiplasmin complex (PAP), and tissue inhibitor of MMP-3 (TIMP-3) levels. MMP levels were determined by enzyme gelatin zymography.Results: The PAI-1 levels were three times higher in HR groups than in controls. Mean PAI-1 levels were almost identical in patients who developed RAO and patients who did not develop RAO. The level of PAP in HR patients was 4-6 times lower than in the control group. MMP-9 activity was 2.5-fold lower in HR group patients who did not develop RAO than in those who developed RAO. In the latter patients, the level of plasma TIMP-3 was 2.3-fold lower than in controls. Mean plasma TIMP-3 level was almost identical in patients who did not develop RAO and LR patients. The mean plasma D-dimer level was the highest in patients who developed RAO; this was 16-fold higher than in the control group, and 11-fold higher than in patients who did not develop RAO.Conclusion: High functional activity of plasmin and proteolytic MMP-9 activity are the major factors of the fibrinolytic system which cause the development of RAO in patients undergoing cardiac surgery. Regulators of plasminogen/plasmin activation (such as PAI-1 and PAP) and TIMP-3 do not play a substantial role in the development of complications in the form of RAO.
Keywords: retina; retinal artery occlusion; valvular heart disease; cardiosurgical interventions; plasminogen/plasmin system; MMP-9